Supplement use by UK-based British Army soldiers in training. Issue 7 (14th August 2014) - Casey, Anna; Hughes, Jason; Izard, Rachel M.; Greeves, Julie P.
Abstract : The use of supplements is widespread at all levels of civilian sport and a prevalence of 60–90 % is reported among high-performance UK athletes, including juniors. The prevalence of supplement use among UK-based British Army personnel is not known. The aim of the present study was to establish the point prevalence of supplement use in UK-based British Army soldiers under training (SuTs) and associated staff. A cross-sectional anonymous survey was carried out in 3168 British Army SuTs and soldiers, equating to 3·1 % of regular Army strength, based at eleven Phase 1, 2 and 3 UK Army training sites. Overall, 38 % of the respondents reported current use of supplements, but prevalence varied according to the course attended by the respondents. The number of different supplements used was 4·7 (sd 2·9). Supplements most commonly used were protein bars, powders and drinks (66 %), isotonic carbohydrate–electrolyte sports drinks (49 %), creatine (38 %), recovery sports drinks (35 %), multivitamins (31 %) and vitamin C (25 %). A small proportion of respondents reported the use of amphetamines and similar compounds (1·6 %), cocaine (0·8 %), anabolic androgenic steroids (1·1 %), growth hormone (2·0 %), and other anabolic agents, e.g. testosterone (4·2 %). Logistic regression modelling indicated that, for current users, younger age, being female, smoking and undergoing Officer Cadet training were associated with greater supplement use. This is the first study to investigate the prevalence of dietary and training supplement use in UK-based British military personnel. Self-administration of a wide range of supplements is reported by British military personnel in training, which is at least as great as that reported by those on deployment, and has implications for Defence policy and educational needs.